WOMEN SOCIO-ECONOMIC STATUS AND POLITICAL PARTICIPATION: A STUDY OF IMO STATE (2015 – 2019) - Anayo Onyeiwu, Emmanuel (African Journal of Social and Behavioural Sciences, 2024)
This study focused on women’s socioeconomic status and political participation in Imo State (2015–2019). The study was carried out to identify the extent of women’s political participation. Two research objectives, two research questions and two research hypotheses, guided the study. For the methodology, a survey research design was used, and a questionnaire served as the instrument for data collection. The population of the study covers all 150 political party executives—50 each from the 3 major political parties (APGA, PDP, and APC) in Imo State and the entire CGC principal executives in the 671 autonomous communities in Imo State, from which 180 were sampled (out of 180 copies of the questionnaire distributed, only 170 were properly filled and returned). The data collected are presented in tables and were analysed via simple percentages, and hypotheses were tested via chi-square tests. Low income discourages women’s political participation, and women’s educational levels affect their ability to stand for an election. On the basis of these findings, it is recommended that the income of women in Nigeria be improved so that women can be financially viable to participate in politics. Moreover, women should be allowed to engage in corporate occupations, which will give them the needed prestige and financial improvement to participate actively in politics.